Answer:
6
Explanation:
Given the expression
, we are to look for the value of the expression when y = 2. To do that we are going to substitute y as 2 into the given expression and simplify the resulting expression as shown.
![f(y) = (2-y)/(4+y) + (3(y+2))/(y)\\\\if \ y = 2;\\\\f(2) = (2-2)/(4+2) + (3(2+2))/(2)\\\\f(2) = (0)/(6) + (3(4))/(2)\\\\\\f(2) =0 + (12)/(2)\\\\\\f(2) = 6](https://img.qammunity.org/2021/formulas/mathematics/high-school/lqfr7xani18zokfqy0oyzhbnuv3ilghf7d.png)
Hence the value of the expression when y = 2 is 6